A combination of second trimester oral metronidazole and no sexual intercourse during second and third trimester may reduce late miscarriage and premature delivery after fertility sparing radical trachelectomy. (October 2021) - Ekdahl, Linnea; Eoh, Kyung Jin; Thumuluru, Kavitha Madhuri; Butler-Manuel, Simon A.; Tae Kim, Young; Lönnerfors, Celine; Falconer, Henrik; Persson, Jan
Highlight: Oral metronidazole and no intercourse may reduce premature birth after trachelectomy. A short post-trachelectomy cervical lenght may impair fertility. Abstract: Objectives: Women with a previous trachelectomy have an increased risk of premature delivery and second trimester miscarriage. In this study we aim to evaluate factors and regimes possibly affecting the risk for prematurity following fertility sparing robotic radical trachelectomy (RRT) in cervical cancer. Methods: A retrospective study of the reproductive outcome following RRT with a cervical cerclage performed at one of four academic centers between 2007 and 2019. Factors possibly related to premature delivery, such as postoperative non-pregnant cervical length, previous vaginal deliveries, preservation of the uterine arteries, and the use of a second trimester oral metronidazole/no sexual intercourse regime, were assessed. Results: 109 women remained for analyses after excluding recurrences before pregnancy ( n = 8), secondary hysterectomy ( n = 2), and women with less than six months follow up ( n = 10). 74 pregnancies occurred in 52/71 women attempting to conceive, 56 of which developed past the first trimester. Two of 22 women (9%) who were prescribed an oral metronidazole regime (400 mg × 2 from gestational week 15 + 0 to 21 + 6 and abstaining from sexual intercourse for the duration of the pregnancy) had a premature delivery, compared with 13/31 (42%) where the regime was not applied ( p = 0.009). The association remained after regression analyses including possible contributing factors as of above, none of which associated with prematurity at regression analyses ( p = 0.001). Conclusions: The observed four-fold reduction in premature delivery indicates that an oral metronidazole/no sexual intercourse regime may reduce second trimester miscarriage and premature deliveries following an RRT. No association was observed for other investigated factors.